1999
DOI: 10.1378/chest.116.4.953
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Among Pulmonary Function, Aerobic Fitness, and Cognitive Functioning in Older COPD Patients

Abstract: In an older COPD sample, age, aerobic fitness, and pulmonary function are predictive of cognitive performance on various tasks. In particular, age and aerobic fitness are predictive of speed of processing, which is a cognitive variable that may itself underlie performance on a majority of cognitive tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
1
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 39 publications
1
44
1
4
Order By: Relevance
“…They may experience age-related declines in blood flow, disease-related declines in arterial oxygen content, and both age-and disease-related declines in physical activity. 24 Our results are partly in agreement with these findings. On the other hand, another study investigating the relationship between aerobic fitness and cognition in a sample of subjects with COPD found that no significant relationships between exercise levels attained and any of the cognitive variables.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They may experience age-related declines in blood flow, disease-related declines in arterial oxygen content, and both age-and disease-related declines in physical activity. 24 Our results are partly in agreement with these findings. On the other hand, another study investigating the relationship between aerobic fitness and cognition in a sample of subjects with COPD found that no significant relationships between exercise levels attained and any of the cognitive variables.…”
Section: Discussionsupporting
confidence: 92%
“…In a study in an older COPD population, the 6-min walk test and pulmonary function tests were predictive of cognitive performance on various tasks. 24 According to the authors, older individuals who have COPD may be affected in 3 ways that are relevant to cognitive functioning. They may experience age-related declines in blood flow, disease-related declines in arterial oxygen content, and both age-and disease-related declines in physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Age-related declines in cognitive function in chronic respiratory disease, such as COPD, were found. 26 However, the mean age of subjects with chronic respiratory disease such as ␤ is the standardized regression coefficient. Statistical significance of P Ͻ .05.…”
Section: Discussionmentioning
confidence: 99%
“…Ayrıca yaşlı KOAH'lı olgularda kognitif fonksiyonların yaşla ilişkili olarak kan akımında azalma, eğitim durumu, hastalıkla ilişkili olarak arteryel oksijen içeriğinde azalma ve hem hastalık hem de yaş ile ilişkili olarak fiziksel aktivitede azalmayla etkilenebileceği belirtilmiştir (18)(19)(20) hasta grubumuzun da hipoksisi olmayan 50 yaş ve üs-tü hastalardan oluştuğu göz önüne alınırsa kognitif fonksiyonlardaki bu azalmada yaş ve KOAH nedeniyle ortaya çıkan sistemik inflamasyon, oksidatif hasar ve fiziksel aktivitedeki kısıtlanmanın rolü olduğu düşünü-lebilir. Ancak hasta ve kontrol grubu arasında yaş ortalamaları ve eğitim düzeyi açısından anlamlı farklılığın bulunmaması ve hasta grubunda SMMT sonuçlarının daha düşük olması KOAH'ın yaştan bağımsız olarak da kognitif fonksiyonlar üzerindeki olumsuz etkisini gös-termektedir.…”
Section: Discussionunclassified